110 MANAGEMENT OF TRANSIENT HYPERGLYCEMIA IN VERY LOW BIRTH WEIGHT INFANTS WITH CONTINUOUS INSULIN INFUSION AND ITS EFFECT ON LACTIC ACID LEVELS. (1st January 2006) - Patil, S.; Cayabyab, R.; Sardesai, S.; Siassi, B.; Seri, I.; Ramanathan, R.
Abstract : Introduction: Transient hyperglycemia (TH) develops in preterm infants on continuous glucose infusion despite receiving glucose infusion rates that matches their basal requirements. This has been attributed to a partially defective processing of proinsulin to insulin and relative insulin resistance requiring higher levels of insulin to achieve euglycemia. Treatment with insulin under euglycemic hyperinsulinemic clamp conditions in 4 clinically stable preterm infants has been shown to result in lactic acidosis. Objective: To evaluate the effect of continuous insulin infusion during TH in sick, very low birth weight (VLBW) infants receiving total parenteral nutrition on lactic acidosis. Study Design: Prospective, observational study of VLBW infants on continuous insulin infusion for TH with measurement of lactate levels. Results: Values are expressed as mean and range. Seven VLBW infants with mean birth weight 738 g (538-1, 263) and mean gestational age 26 wks (range 24-30) were on continuous insulin infusion for TH. All infants were on parenteral nutrition receiving protein and intralipids in addition to glucose initiated within 12 to 24 hours of life. Mean blood sugar level was 235 mg/dL (180-334) prior to start of insulin infusion at a mean dose of 0.04 U/kg/hr (0.01-0.05). Mean glucose infusion rate was 6.9 mg/kg/min (4.7-10.5). Mean lactate level prior to start of insulin infusion was 3.2 (0.7-8.1mmol/L) and mean lactate levels post insulin was 1.5 (0.5-3.8 mmol/L). Four of the 7 infants required 2 to 4 courses of insulin infusions for TH. One of the 4 neonates was septic with a congenital E. coli infection, and 3 were severely compromised at birth, requiring the use of pressors to stabilize their blood pressure. All infants received 1-3 insulin boluses of 0.1 unit/kg/dose prior to starting the insulin infusion. In all instances, the post-insulin infusion lactic acid levels were lower. None of the infants developed hypoglycemia during insulin infusion. Conclusions: The use of continuous insulin infusion with or without an initial bolus dose for transient hyperglycemia in sick, VLBW infants is not associated with the development of lactic acidosis but may actually improve the preexisting acidosis. Our results are in favor of insulin infusion to correct the transient metabolic abnormalities and to maintain biological levels of insulin to achieve euglycemia during TH.